Effect of sodium alginate coating containing clove (Syzygium Aromaticum) and lemon verbena (Aloysia Citriodora) essential oils and different packaging treatments on shelf life extension of refrigerated chicken breast. Issue 3 (29th January 2021) - Hosseini, Mahzad; Jamshidi, Abdollah; Raeisi, Mojtaba; Azizzadeh, Mohammad
Abstract: The present study was conducted to preserve the microbial quality of chicken breast during storage time by using sodium alginate active coating solutions incorporated with different natural antimicrobials including Lemon Verbena (Le) and clove essential oils (Cl) which were added individually and in combination as well as packaging in Modified Atmosphere (M) (65% CO2, 30% N2, and 5% O2 ) and in ambient atmosphere (A). The samples were stored in refrigeration condition for 15 days and were analyzed for total viable count, Enterobacteriaceae count, lactic acid bacteria count, Pseudomonas spp. count, psychrotrophic count, and yeast and mold count, as well as pH, TBA, TVN, and sensory analyses at 5‐day intervals. After 15 days of storage it was found that coating with sodium alginate containing 0.5% of Cl and 0.5% Le in modified atmosphere packaging is the most effective combination in lowering aerobic mesophilic bacteria, Pseudomonas, Psychrotrophic bacteria, Enterobacteriaceae, mold, and yeast. Results indicated that Le0.5 C0.5 M had the lowest pH (5.76) after 15 days. Lipid oxidation increased rapidly after 5 days of storage all treatments while minimum TBA values were recorded in Le0.5 C0.5 M treatments the lowest TBA values were obtained (0.54 mg MDA/kg). Le0.5 C0.5 M and Le0.5M showed the least TVN after 15 days (36.66 mg/100 g). Sensorial analysis showed no significant differences between coated and uncoated samples. In conclusion, using MAP with essential oils led to increases the antibacterial effect of essential oils against both gram‐positive and gram‐negative tested bacteria and play a major role on increasing the shelf life of chicken breast. Practical applications: There are various challenges associated with chicken products throughout their shelf life as they are highly prone to microbial and chemical spoilage. The adverse effects of various chemical preservatives caused to attract the consumer's attention to natural alternatives. Hence, new processing technologies and new ingredient systems that are associated with natural and organic foods are applied. The results of the study demonstrate the potential combined use of alginate coating, modified atmosphere packaging, and Clove and Lemon Verbena Essential Oils to the chicken and meat industry in the development of novel healthy meat products with improved shelf life and superior product quality.